Anxiety Level of Pregnant Women at Siti Khodijah Muhammadiyah Sepanjang Hospital During COVID-19 Pandemic - Dwi Ariningtyas, Ninuk; Islamy, Aulia Nuril; Subagyo, Roni; Anas, Muhammad (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2024)
Pregnant women are one of the vulnerable groups who have to face the unpleasant effects of the COVID-19 pandemic. One of the effects is the psychological impact that is bad for both the mother and the fetus. This study aims to describe the level of anxiety experienced by pregnant women during the COVID-19 pandemic at Siti Khodijah Muhammadiyah Sepanjang Hospital. The results of this study are expected to be used as information to help overcome more serious mental health problems. This research uses using quantitative descriptive design with a cross-sectional approach. The sample of this study was 112 pregnant women who met the research criteria. This research was conducted by giving them questionnaires consisting of their age, job, parity, gestational age, history of COVID-19 illness, history of mental problems, knowledge about COVID-19, and level of anxiety. Statistical analysis showed 84.8%, 8.9% and 6.3% of pregnant women experience low, moderate, and concerning levels of anxiety, respectively. The majority of pregnant women are primigravida, aged 20-35 years, with a gestational age of 28-41 weeks, housewives, and the level of knowledge about COVID-19 is very good. Correlation analysis using Kendall's tau-b showed a significance value of 0.038 (<0.05), which means a relationship exists between the level of knowledge about COVID-19 and the level of anxiety of pregnant women. In conclusion, the level of anxiety of pregnant women the most is low anxiety, followed by moderate and concerning levels of anxiety.